MIMO Cognitive Radio with Low Cost Reception Using Beam Forming And Antenna Sub Array Formation - Arpitha Shankar, SI (International Journal of Computer Sciences and Engineering, 2025)
A Cognitive Radio is a Software Defined Radio (SDR).The Cognitive radio network is capable to sense and analyze its surrounding environment as well as reconfigure its operation in accordance with this radio environment. In this way, based on the available Channel State Information (CSI), the cognitive radio network may dynamically access the spectrum. MIMO based cognitive radio system enabled dynamically simultaneous usage of a radio spectrum for this beam forming signal processing technique is used. Beam forming is a technique in which the directionality of transmission and reception of radio signals can be controlled. Modern wireless technology depends on beam forming technology in order to provide higher data rates, improved coverage and also used to share the spectrum with the other users. Hardware complexity is one of the main issue in MIMO based wireless system which require N number of RF chains for N antenna systems. Antenna sub array formation (ASF) scheme is an optimization technique which can be used to reduce the RF chain required such a way the capacity can be improved. This will reduce the cost of the hardware much and we can realize low cost hardware system. Usually the two process of sub array formation and beam forming are done as separate process but in this paper the joint beam forming and sub array formation is done such a way the secondary user capacity will be improved and to avoid two computational complex process. Antenna sub array formation (ASF) scheme is employed to maximize the Signal to Interference Ratio (SINR) by using all antenna elements. In Antenna sub array formation the Radio Frequency chain is allocated to sub array of elements.